The Effects of Andrographis Paniculata (Burm. f.) Nees Extract on the Liver White Rats (Rattus norvegicus L.) induced by Lead Acetate - Andrian, Luthfiyah; Febriani, Husnarika; Tambunan, Efrida Pima (Jurusan Biologi Universitas Negeri Makassar, 2024)
Lead acetate is classified as a heavy metal compound that has the ability to stimulate the overproduction of free radicals, sometimes referred to as Reactive Oxygen Species (ROS), leading to oxidative stress at the cellular level. When lead acetate is introduced into the body, it undergoes systemic circulation and distributes to several organs, including the liver. Prolonged exposure of the liver to high levels of lead can result in hepatic damage. The leaves of Andrographis paniculata (Burm. fil.) Ness are known to possess antioxidant properties, rendering them suitable for medicinal use in combating free radicals. The objective of this study is to investigate the impact of ethanol extract derived from Andrographis paniculata (Burm. fil.) Ness on the morphological characteristics and hepatic functionality of white rats (Rattus norvegicus L.) that have been treated with lead acetate. The present study employed a completely randomized design, consisting of five treatment groups and five repetitions. The control group received only food and drink, while the experimental group was administered lead acetate for a duration of 28 days at a dosage of 40 mg. The treatment groups, on the other hand, were each administered ethanol extract of Sambiloto leaves at dosages of 250, 500, and 750 mg/kg BW for a period of 14 days. The findings indicated that the treatment of lead acetate resulted in liver histological damage, specifically parenchymatous degeneration, hydropic degeneration, and necrosis. Additionally, it led to elevated levels of SGPT and SGOT. The study's findings indicate that the administration of a 750 mg/kg BW dose of ethanol extract derived from Sambiloto leaves can effectively mitigate liver histological damage and lower levels of SGPT and SGOT.